Management of dystocia due to multiple mal-dispositions in a Marwari mare - Kumar, Amit; Mahal, Jugraj Singh; Bisla , Amarjeet; Honparkhe, Mrigank (The Indian Journal of Animal Reproduction, 2022)
A Marwari mare with history of dystocia since last twelve hours was presented to the gynecology section of teaching veterinary clinics of GADVASU. Per vaginal examination revealed multiple fetal mal-dispositions as the cause of dystocia. After lubrication of birth canal, fetal position was corrected by mutation and the dead fetus was delivered using forced traction. Post-operative treatment was given to the mare. There was an uneventful recovery of the mare.